2021
DOI: 10.20944/preprints202111.0304.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Functional Characterization of Transporters for L-Aspartate in Bacillus licheniformis

Abstract: Amino acid efflux and influx transport systems play vital roles in industrial microorganisms’ cell growth and metabolism. However, although biochemically characterized, most amino acid transporters remain unknown at the molecular level in Bacillus licheniformis. This study focuses on the molecular and functional characterizations of three transporters, YdgF, YvbW, and YveA, mainly when catalyzing the cross-membrane flux of L-Aspartate. When growing in the minimal medium with L-Asp as the only carbon … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…Interestingly, supplementation with GPS further increased microbial richness in mice fed with the HFD diet. Cyclic enol ether terpenoids have been reported to increase the α-diversity of microbiota in HFD-fed mice (Zhang L. et al, 2021). The main phyla of gut microbiota species distribution include, Firmicutes and Bacteroidetes, followed by two minority phyla, Actinobacteriota and Proteobacteria Actinobacteria and Aspergillus, and the rest belong to Verrucomicrobiota and Clostridium (Delik et al, 2022), among others.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, supplementation with GPS further increased microbial richness in mice fed with the HFD diet. Cyclic enol ether terpenoids have been reported to increase the α-diversity of microbiota in HFD-fed mice (Zhang L. et al, 2021). The main phyla of gut microbiota species distribution include, Firmicutes and Bacteroidetes, followed by two minority phyla, Actinobacteriota and Proteobacteria Actinobacteria and Aspergillus, and the rest belong to Verrucomicrobiota and Clostridium (Delik et al, 2022), among others.…”
Section: Discussionmentioning
confidence: 99%
“…217 In vitro and preclinical studies on docetaxel-loaded CNTs in PC3 and S180 (murine sarcoma) cell lines have shown that they are more impactful than free docetaxel. 218 In another study, the efficacy of PEGylated nanotubes incorporated with a chemotherapeutic agent was studied with regard to its mitochondrial apoptosis, cytotoxic profile in NSCLC, its cellular uptake and dynamics. The authors attempted to see that the compound was mostly received by clathrin-mediated endocytosis, which would help the A549 cell line generate early endosomes.…”
Section: Nanocarrier-mediated Drug Delivery Systemsmentioning
confidence: 99%